Meningkatkan Hasil Belajar Siswa Pada Materi Pecahan Melalui Model Pembelajaran Kontekstual - Misrina Misrina (PGMI IAIN Lhokseumawe, 2022)
This study aims to increase the activity and learning outcomes of fifth grade students at SD Negeri 12 Samalanga in fractional material through a contextual learning model. This research is a classroom action research conducted in two cycles. The data source in this study, were 16 of class V students at SD Negeri 12 Samalanga, Bireuen Regency. The results of the study show that learning with a contextual approach can improve student learning outcomes at SD Negeri 12 Samalanga, Bireuen Regency in fraction material. This can be seen from the results of the implementation of the tests that the researchers carried out, where in the implementation of the initial tests the percentage of learning completeness was obtained as much as 31.25%, there was an increase in cycle I to 62.5% in, and cycle II increased again to 87.5%. Observational data also showed an increase from cycles I and II. Cycle I data shows the percentage of achievement is 74.86% and Cycle II is 89.27%.